Improvement Students' Understanding of Worship Through Use of Practical Videos Performing ablution at Iman Syafi'i Islamic Elementary School Bima City - Nur Insyania; Husnatul Mahmuda; Kaharuddin (Lembaga Bale Literasi, 2026)
The purpose of this study was to determine the improvement in students' understanding of worship through the use of ablution practice videos at SD IT Iman Syafi'i , Bima City. This study used a qualitative approach with a descriptive type. Data collection techniques were carried out through observation, interviews, and documentation, while data validity used triangulation of sources, techniques, and time. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study showed that there was an increase in students' understanding of worship through the use of ablution practice videos at SD IT Iman Syafi'i , Bima City, that the increase in students' abilities in understanding and practicing ablution after participating in this activity showed that the combination of the use of audiovisual media, live demonstrations, and guided practice was an effective learning strategy for procedural fiqh material.